Diseño para servir - Mathur, Vishwa N.P. (Instituto de Ecología, A.C., 1995)
Wood structures have been used in North America since prehistoric times. Only after the arrival of the first European settlers, the light frame structure system was developed in this part of the continent. This paper presents a series of ideas about the best ways to make more adequate use of wood characteristics and about the necessary processes to obtain successful designs. The three main rules for achieving maximum performance in the use of wood in structures are: 1) Use dry wood, 2) keep it dry and 3) treat the wood with a suitable preservative to protect it from destructive organisms. Architectural examples of wood buildings in Canada are provided and these give an idea of the great variety of solutions available to architects, the flexibility of the proposed systems and their adaptability with respect to a wide variety of situations and types of construction.